1987
DOI: 10.1037/0022-0167.34.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Relation of depression and help-seeking history to attitudes toward seeking professional psychological help.

Abstract: We investigated the relation of help-seeking history, sex, and depression to college students' attitudes, beliefs, and intentions about obtaining professional psychological help. College students completed questionnaires that included the Beck Depression Inventory (Beck, Ward, Mendelson, Mock, & Erbaugh, 1961), an inquiry about help-seeking history, and an attitude scale constructed according to the method posited in the theory of reasoned action (Ajzen & Fishbein, 1980). Of these 429, 126 who represented extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 40 publications
(58 reference statements)
4
50
0
4
Order By: Relevance
“…For example, several researchers have suggested that a better understanding of people's helpseeking behavior could be gathered by using Ajzen and Fishbein's (1980) theory of reasoned action (TRA; Bayer & Peay, 1997;Codd & Cohen, 2003;Halgin, Weaver, Edell, & Spencer, 1987). Specifically, TRA asserts that people's actions are decided through a series of rational judgments.…”
mentioning
confidence: 99%
“…For example, several researchers have suggested that a better understanding of people's helpseeking behavior could be gathered by using Ajzen and Fishbein's (1980) theory of reasoned action (TRA; Bayer & Peay, 1997;Codd & Cohen, 2003;Halgin, Weaver, Edell, & Spencer, 1987). Specifically, TRA asserts that people's actions are decided through a series of rational judgments.…”
mentioning
confidence: 99%
“…[25][26][27] According to the theory of reasoned action, intention is the critical determinant of behavior. Intention is determined by beliefs and attitudes about treatment behaviors (eg, medication effi cacy and adverse effects), subjective social norms (eg, concern with regard to family opinions), past behavior (eg, past treatment), perceived behavioral control (eg, theory of planned behavior), and self-effi cacy.…”
mentioning
confidence: 99%
“…Deane i Chamberlain 1994;Kelly & Achter 1995;Deane & Todd 1996;Bayer & Peay 1997;Cepeda-Benito & Short 1998;Cramer 1999;Carlton & Deane 2000) nedvosmisleno pokazuju da osobe koji imaju pozitivne stavove prema traženju profesionalne psihološke pomoći snažnije izražavaju nameru da traže pomoć, u odnosu na osobe koje imaju negativne stavove prema traženju profesionalne psihološke pomoći Takođe su značajni i rezultati brojnih istraživanja (npr. Halgin et al 1987;Deane & Todd 1996;Bringle & Byers 1997;Carlton & Deane 2000;Ciarrochi et al 2002) koji pokazuju da je postojeće iskustvo u traženju profesionalne psihološke pomoći pouzdan pokazatelj namere da se profesionalna psihološka pomoć traži i u sadašnjosti, odnosno u budućnosti, ukoliko postoji potreba za njom.…”
Section: Uvodunclassified